From Intellectual to Advocacy Movement: Islamic Moderation, the Conservatives and the Shift of Interfaith Dialogue Campaign in Indonesia - Wasisto Raharjo Jati; Halimatusa'diah Halimatusa'diah; Syamsurijal Syamsurijal; Gutomo Bayu Aji; Muhammad Nurkhoiron; Riwanto Tirtosudarmo (Ulumuna, 2022)
The interfaith dialogue campaign takes a new turn after the demise of the authoritarian regime in 1998. While the previous campaign was characterized by the important role of public intellectuals, such as Gus Dur, Romo Mangunwijaya and Th. Sumartana; the new generation of campaigners adopt more community-based advocacy movement. The shift into a new turn specifically refers to two phenomena; 1) change of the modes and practices of interfaith dialogue movement at the society level and 2) the idea of recent interfaith originates more from communities rather than from prominent public intellectuals. These two phenomena basically show the opportunities and challenges for the future of interfaith dialogue campaign. The study uses two methods, namely archival and case study based on the empirical data from Makassar and Yogyakarta in the mid 2022. The findings show that advocating interfaith dialogues through communities as adopted by the new generation of campaigners apparently more effective for young generations than what is experienced before 1998. It generates the recent interfaith dialogue among young people to be intimate. The findings also implies that the religious moderation discourse and campaign recently propagated by the Ministry of Religious Affairs need to be critically assessed. These two findings interestingly show the conservatives’ involvement that eager to join interfaith campaign in order to curb hardliner stigma.